Tourist popularity of Poland among the inhabitants of Stavropol Krai - Zawadka, Jan; Ivolga, Anna (Turystyka i Rozwój Regionalny, 2017)
The article presents the tourist popularity of Poland among the inhabitants of Stavropol Krai (a region located in the south of the European part of the Russian Federation). The research attempted to identify the reasons for discouraging the inhabitants of this region to take a tourist trip to Poland. Also presented the reasons, ways of organization and opinions on the tourist attractiveness of Poland against the background of selected countries among the people who visited Poland. The survey, in the form of an internet survey, was conducted among 141 inhabitants of Stavropol Krai. Based on the results of the research it can be stated that for the inhabitants of this region Poland is an attractive tourist country. However, it must be emphasized that much is still to be done to promote Poland as an attractive tourist destination. A large part of the respondents were not aware of its tourist attractiveness, which was the main reason for the lack of interest in this country.